Desmopressin for the treatment of adult nocturia. Issue 5 (September 2008) - Hashim, Hashim; Abrams, Paul
Nocturia is a bothersome and prevalent condition. It affects men and women equally, with an increasing incidence with age. It has multifactorial etiology and therefore treatment is based on an accurate history and examination with an assessment that should include frequency/volume charts and quality-of-life questionnaires. Treatment is primarily aimed at the etiology and may include referral to an appropriate specialist for administration of specific treatments. Initial treatment is based on lifestyle advice including fluid manipulation. If nocturia is of polyuric origin and is caused by a disturbance in the vasopressin system, the only efficacious medical treatment available with a good level of evidence is desmopressin. This review will look at the pharmacology of desmopressin and will review the evidence in the literature that would support its use in nocturia. Sometimes combination therapy with antimuscarinics and αα-blockers may be required to control nocturia secondary to storage and voiding problems associated with nocturnal polyuria; however, no trials have actually looked into this concept to date.